Implementation of the e-retribution system in the wholesale market for vegetables, fruit and food commodities Pare district of Kediri - Khariroh, Sururin; Yuana, Yuana (Prosiding Seminar; 2022: 2022 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.73, 2023)
the aims was to analyasis of problem solving implementation e-retribution of pare market at Kediri district. This research was a qualitative study by collecting data from various books and journals as well as through field observations. The results showed that the implementation of e-retribution used to solve problems that arise is to collect data on traders which are then inputted into the merchant database and implement an E-retribution system prepare SOPs for implementing this system. E-levies are considered effective in reducing levy leakages, reducing extortion practices and providing accurate and accountable data. The implementation of the levy collection system before the existence of the E-levy system was carried out manually with cash payments. The problems faced before the E-retribution system were levy leaks and extortion practices in the field. The cause of problems at the Vegetable and Food Commodity Main Market Pare is because the manual and cash collection system cannot provide valid data about the total amount of fees collected, so that when setting targets and potential it does not reflect the real conditions on the ground